Implementación de analítica de datos sobre datos geoespaciales en una aplicación de micro-localización que sirva para generar un software de guía dentro de la Universidad Politécnica Salesiana Campus Sur - Valencia Asqui, Patricio Ulices (2017)
Advances in Information and communications technology (ICTs) and the use of micro-location are improving the information services that can be provided in a geographical area, institution, and to the general public, giving relevant information in real-time conglomerating a vast group of populated places such as conferences, buildings, tourist sites, and populated places in general that are in their geographical location. This research seeks to implement this new technology, enabling students, teachers, and the public to actively interact with the micro-localization services that are intended to be provided at the Salesiana Polytechnic University. For the implementation of this technology, the MIDANO methodology was used. This document is organized in four chapters, it begins with a quick introduction to data analytics, and the MIDANO methodology, then the description of the mobile application using the previous methodology and the different tools that were used for its implementation, as well as for the emulation of beacons that allow the link between the event notification and the generated mobile application (prototype), to finally show the results and application in an experimental context at the Salesiana Polytechnic University campus south.